Digitalisasi Ekonomi Kota Medan: Peran E-Commerce dan Startup Lokal dalam Meningkatkan Pertumbuhan Ekonomi - Irsyadiah Dermaini Berutu; Purnama Ramadani Silalahi (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Economic digitalization has become a key driver of growth in various regions, including Medan City. The development of e-commerce and local startups plays a vital role in this economic transformation by enhancing market access, accelerating product distribution, and creating new job opportunities. E-commerce allows business owners to reach a broader consumer base, while local startups foster innovations tailored to the needs of Medan's society. This paper aims to analyze the role of e-commerce and local startups in enhancing economic growth in Medan City, as well as the challenges and opportunities within this digital ecosystem. The findings suggest that these two sectors complement each other in creating an inclusive and sustainable economic ecosystem.